1996
DOI: 10.1159/000109183
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression and Transcription Factor Binding Activity during Cellular Aging

Abstract: Human diploid fibroblasts (HDFs) undergo a limited number of population doublings in vitro and are widely used as a model of cellular aging. Despite growing evidence that cellular aging occurs as a result of altered gene expression, little is known about the activity of transcription factors that regulate gene expression in aging cells. Here we survey the relevant literature regarding altered gene expression and the role of transcription factors during cellular aging, focusing upon the serum response factor (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…As shown previously, most cells expressing oncogenic ras alone displayed a cytoplasmic staining for phospho-ERK1/2. This finding is consistent with reports indicating that senescent cells do not respond to serum stimulation (28). However, more than half of the cells expressing the anti-PEA-15 hairpin exhibited a predominant nuclear staining of phospho-ERK1/2 (Fig.…”
Section: Pea-15 Erk Localization and Senescencesupporting
confidence: 92%
“…As shown previously, most cells expressing oncogenic ras alone displayed a cytoplasmic staining for phospho-ERK1/2. This finding is consistent with reports indicating that senescent cells do not respond to serum stimulation (28). However, more than half of the cells expressing the anti-PEA-15 hairpin exhibited a predominant nuclear staining of phospho-ERK1/2 (Fig.…”
Section: Pea-15 Erk Localization and Senescencesupporting
confidence: 92%
“…Changes in the expression patterns of a number of cell cycle-regulatory genes during replicative senescence, some of which are thought to contribute to the senescent phenotype, have been described (42,69 (2,16,21,47,72). Interestingly, we and others have found that the activity of p53 increases in senescent fibroblasts (3,66), perhaps providing a molecular mechanism for the upregulation of D-type cyclins during cellular aging.…”
Section: Waf/cip/sdimentioning
confidence: 66%
“…3e), however. Third, phosphorylation of SRF by the ribosomal S6 kinase pp90RSK, casein kinase II, or DNA-PK can enhance its transcription-promoting activity and DNA binding (37,(41)(42)(43)(44)(45)(46)(47)(48)(49). Whether differential phosphorylation of SRF contributes to the differences in binding activity observed in our subconfluent or long term serum-deprived cells requires further study.…”
Section: Discussionmentioning
confidence: 91%